The Association of microRNA-34a With High Incidence and Metastasis of Lung Cancer in Gejiu and Xuanwei Yunnan - Chen, Yan; Hou, Chun; Zhao, Liu-xin; Cai, Qiu-chen; Zhang, Ying; Li, Da-lun; Tang, Yao; Liu, Hong-yu; Liu, Yun-yi; Zhang, Yue-yan; Yang, Ya-kun; Gao, Cheng-wei; et al. (Frontiers in Oncology, 2021)
The incidence and associated mortality of lung cancer in tin miners in Gejiu County and farmers in Xuanwei Country, Yunnan Province have been very high in the world. Current published literatures on the molecular mechanisms of lung cancer initiation and progression in Gejiu and Xuanwei County are still controversial. Studies confirmed that microRNA-34a (miR-34a) functioned as a vital tumor suppressor in tumorigenesis and progression. However, the role and precise mechanisms of miR-34a and its regulatory gene network in initiation and progression of lung cancer in Gejiu and Xuanwei County, Yunnan Province, have not been elucidated. In the current study, we first found that miR-34a was downregulated in Gejiu lung squamous carcinoma YTMLC-90, Xuanwei lung adenocarcinoma XWLC-05 and other non-small cell lung carcinoma (NSCLC) cell lines, and miR-34a overexpression inhibited cell proliferation, migration and invasion, as well as induced cell apoptosis in YTMLC-90 and XWLC-05 cells. Our findings revealed that miR-34a is critical and cannot be considered as the area-specific non-coding RNA in initiation and progression of lung cancer in Gejiu and Xuanwei County. Next we revealed that miR-34a overexpression suppressed lung cancer growth and metastasis partially via increasing PTEN but reducing CDK6 expression that might lead to subsequent inactivation of PI3K / AKT pathway. Furthermore, our findings demonstrated that YY1 functioned as a tumor suppressor gene in initiation and progression of lung cancer in Gejiu and Xuanwei County. In conclusion, our findings in the study confirmed that miR-34a overexpression could simultaneously suppress tumor growth and metastasis and play a vital role in tumorigenesis and progression of NSCLC via increasing PTEN and YY1 expression, but decreasing CDK6. Most interestingly, our findings also raised doubts about the current ideas about these area-specific diseases.